2013
DOI: 10.1038/oncsis.2013.12
|View full text |Cite
|
Sign up to set email alerts
|

RAF kinase inhibitor-independent constitutive activation of Yes-associated protein 1 promotes tumor progression in thyroid cancer

Abstract: The transcription coactivator Yes-associated protein 1 (YAP1) is regulated by the Hippo tumor suppressor pathway. However, the role of YAP1 in thyroid cancer, which is frequently associated with the BRAFV600E mutation, remains unknown. This study aimed to investigate the role of YAP1 in thyroid cancer. YAP1 was overexpressed in papillary (PTC) and anaplastic thyroid cancer, and nuclear YAP1 was more frequently detected in BRAFV600E (+) PTC. In the thyroid cancer cell lines TPC-1 and HTH7, which do not have the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
4
16
1
Order By: Relevance
“…30 Likewise, similar experimental data obtained in a prior study published by Liu et al 27 revealed that the expression levels of autophagy markers, including Beclin-1, LC3I 30 Likewise, similar experimental data obtained in a prior study published by Liu et al 27 revealed that the expression levels of autophagy markers, including Beclin-1, LC3I…”
Section: Silencing Of Tnrc6c-as1 Inhibited Tumorigenesis In Nude Micesupporting
confidence: 64%
“…30 Likewise, similar experimental data obtained in a prior study published by Liu et al 27 revealed that the expression levels of autophagy markers, including Beclin-1, LC3I 30 Likewise, similar experimental data obtained in a prior study published by Liu et al 27 revealed that the expression levels of autophagy markers, including Beclin-1, LC3I…”
Section: Silencing Of Tnrc6c-as1 Inhibited Tumorigenesis In Nude Micesupporting
confidence: 64%
“…Ligand-specific receptor tyrosine kinase activation is a druggable target in RAI-refractory thyroid cancers (36)(37)(38). Recently, MEK-ERK independent signaling pathways involved in thyroid carcinogenesis have been investigated (39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…The cascade of MST1/2 and LATS1/2 signalling was demonstrated to inactivate YAP1 by promoting its inhibitory Ser127 (S127) site phosphorylation, cytoplasmic retention and proteasome-mediated degradation 34 . Activation of YAP1 due to the gene amplification or the loss-of-function of MST1/2 or LATS1/2 is linked to the aetiology of many cancers including lung 35 , colon 36 , ovarian 37 , head and neck 38 , liver 39,40 , meningioma 41 , thyroid 42 and stomach 43 . In addition, emerging evidence suggests that YAP1 may also play a critical role in the pathobiology of PC 44 .…”
mentioning
confidence: 99%